Implementasi Pancasila Dalam Menangkal Intoleransi, Radikalisme Dan Terorisme - Agus Subagyo (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2020)
This paper wants to explain and analyze about Pancasila as the ideology of the Indonesian state as a solution / medicine to solve the problem of intolerance, radicalism, and terrorism, which lately is rife in society. Pancasila can be used as an antidote in eradicating intolerance, radical behavior and acts of terror, which endanger national security and the integrity of the Indonesian state. The values contained in Pancasila, whether God, Humanity, Unity, Consensus, and Justice, must be earthed, practiced, and applied in the life of the nation, state and society. Pancasila must become a code of conduct, value system and system of movement for the Indonesian people.